2023
DOI: 10.1002/app.54003
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐polyols synthesized by liquefaction of cellulose: Influence of liquefaction solvent molecular weight

Abstract: Currently, the plastics industry including polyurethanes is based on the use of petrochemicals. For this reason, scientists are looking for new types of renewable resources for the substitution of petrochemical substances. This work aims to evaluate the effect of polyethylene glycols (PEG) with different molecular mass impact on properties of bio-based polyols synthesized via biomass liquefaction of cellulose. To date, research has mostly focused on the use of different biomass sources, but the area of bio-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…The third degradation step which occurs in the range from 375 to 450 °C may be connected to the degradation of soft segments which are composed of petrochemical polyol (ELAPOL) and polyethylene glycol (PEG) parts of bio-based polyol 47 . The degradation of polyethylene glycol (PEG) parts of bio-based polyol was confirmed in our previous studies 31 , where thermogravimetric analysis showed a peak of intensive polyol degradation at around 375–392 °C. At temperatures above 450 °C the peak overlapping with the peak of the third degradation step can be noticed and may be due to the thermolysis of degradation products formed during previous degradation steps.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The third degradation step which occurs in the range from 375 to 450 °C may be connected to the degradation of soft segments which are composed of petrochemical polyol (ELAPOL) and polyethylene glycol (PEG) parts of bio-based polyol 47 . The degradation of polyethylene glycol (PEG) parts of bio-based polyol was confirmed in our previous studies 31 , where thermogravimetric analysis showed a peak of intensive polyol degradation at around 375–392 °C. At temperatures above 450 °C the peak overlapping with the peak of the third degradation step can be noticed and may be due to the thermolysis of degradation products formed during previous degradation steps.…”
Section: Resultssupporting
confidence: 58%
“…On the other hand, it should be noted that the difference in thermal stability between samples with the addition of different polyols is not significant. The thermal stability of bio-based polyols was determined during our previous studies 31 .
Figure 4 Thermogravimetric (TG) curves of foams with addition of bio-based polyols; ( a ) P_200; ( b) P_400; ( c ) P_600.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the ratios of liquid solvent to solid biomass are usually relatively high in order to result in a complete conversion of the wood waste. As an example, Olszeweski et al, 2023, displayed that it was possible to achieve the liquefaction of a cellulose sawdust waste with a yield of approximately 95%, but the ratio of solid to liquid had to be increased to 1:10 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%